2021
DOI: 10.1111/imb.12748
|View full text |Cite
|
Sign up to set email alerts
|

Sexual diversification of splicing regulation during embryonic development in honeybees (Apis mellifera), A haplodiploid system

Abstract: The honeybee is a haplodiploid organism in which sexual development is determined by the complementary sex determiner (csd) gene and realized by sex-specific splicing processes involving the feminizer (fem) gene. We used high throughput transcriptome sequencing (RNA-Seq) to characterize the transcriptional differences between the sexes caused by the fertilization and sex determination processes in honeybee (Apis mellifera) embryos. We identified 758, 372 and 43 differentially expressed genes (DEGs) and 58, 176… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…The male splice variant of the fem transcript is produced by default 25 , 26 . We performed female and male embryonic transcriptome sequencing 27 and searched for sex-specific splice junctions that are only present in females but not in males (Fig. 1b ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The male splice variant of the fem transcript is produced by default 25 , 26 . We performed female and male embryonic transcriptome sequencing 27 and searched for sex-specific splice junctions that are only present in females but not in males (Fig. 1b ).…”
Section: Resultsmentioning
confidence: 99%
“…The exon structure of glu ( LOC552468 ) in A. mellifera was determined using RNAseq data 27 and the amplicon sequences obtained via RT-PCR using RNA derived from 25 to 40 h old male and female honeybee embryos and brain tissues of female pupae. Domain searches were conducted with PROSITE ( https://prosite.expasy.org/ ) 57 , InterPro ( https://www.ebi.ac.uk/interpro/ ) 58 , and the Pfam database ( https://pfam.xfam.org ) 59 .…”
Section: Methodsmentioning
confidence: 99%
“…The transgenic work also showed that the shift to female splicing in transgenic haploids was not complete [the splice regulation in female diploids involves regulatory feedback at the level of fem transcript splicing ( 21 )], indicating that we cannot fully mimic the diploid female condition using transgenes in haploid genetic males. Possibly, the haploid bees lack factors that are only expressed in diploids as our embryonic gene expression study suggests ( 50 ). However, the genetic work in this study suggests that the gene products expressed from different and identical csd allele combinations must be recognized to determine sex.…”
Section: Discussionmentioning
confidence: 99%
“…For example, B. tabaci, as a member of the order Hemiptera, is assumed to undergo embryo development with in a similar time frame and using the same embryo patterning scheme. However, B. tabaci uses a haplodiploid sex determination system, which is almost exclusively studied in Holometabola and is known to affect developmental patterning and morphogenesis (Netschitailo et al, 2022). However, due to a lack of embryological studies, it is unknown to what extent hemimetabolous embryo development is evolutionarily conserved in B. tabaci or how their sex determination system affects their patterns of development.…”
Section: Introductionmentioning
confidence: 99%